Fundamental Study On The Effect Of Lekhaniya Mahakashaya In Santarpanjanya Vyadhi W.R.T. Sthaulya (Obesity) (International Journal of Environmental Sciences, 2025)
Ati Sthula is defined as a person who owing to an inordinate increase of fat and flesh is distinguished with pendulous buttocks, belly, and breasts and whose increased bulk does not match with a corresponding increase in energy. Obesity is a medical condition in which excess body fat has accumulated to the extent that it may have an adverse effect on health. It is defined by body mass index and further evaluated in terms of fat distribution via the waist-hip ratio. Energy consumption in excess of energy expenditure leads to obesity on an individual basis.Aim-To assess the effect of LekhaniyaMahakashaya in the management of SthaulyaMethod- probable mode of action of decoction of lekhaniyamahakashaySthaulya is caused by hypo functioning of Medo Dhatvagni as a result of this Condition Dushta Medo Dhatu is increased in the body. As per Sushruta, the drug which performs Lekhana Karma is the main constituent of Vayu and Agni Mahabhuta hence the properties of LekhaniyaMahakashaya.Result- Here the ayurvedic medicines like LEKHANIYA MAHAKASHAYA has been proved to be effectiveandsignificantConclusion-The response to treatment was good in each patient, and the data was statistically significant. So, the therapeutic response among the patients included in this study was encouraging.Thus, it can be concluded that LekhaniyaMahakashayaKwath is proven to be an effective therapy and this regimen should be tested on large scale for a long duration of the trial with better parameters.Thus, in this study,Null Hypothesis(H0) is rejected and Alternative Hypothesis(H1) is accepted.